The use of real-time ultrasound to model the growth performance and lysine requirements of growing-finishing pigs on commercial farms - J W Smith II; A P Schinckel; Michael D Tokach; Jim L Nelssen; Robert D Goodband; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 1996)
Eighty pigs, 40 barrows and 40 gilts, on two commercial finishing operations were used to model growth and accretion rates. Major differences were observed between the two farms. This analysis indicates that real-time ultrasound can be used to develop lean and lipid accretion curves for formulating farm-specific diets that optimize lean growth performance in commercial operations; Swine Day, Manhattan, KS, November 21, 1996
Keywords: Swine day; 1996; Kansas Agricultural Experiment Station contribution; no. 97-142-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 772; Swine; Ultrasound; Growth; Modeling; Performance